Improving business process performance : gain agility, create value, and achieve success - Raynus, Joseph (Boca Raton, FL : CRC Press, 2011)
'The managerial practices that drove industry for decades have become increasingly insufficient to support the increasing rate of change. Without adequate quantitative understanding of the progress made to achieve organizational goals, corporations quickly lose their competitive edge. They are constantly challenged to reshape their operations, improve performance, and adapt swiftly to new markets and opportunities. Yet with new methodologies and frameworks such as BPM, BPI, Six Sigma, Lean, and Executive Dashboard, many question where to begin. This text surveys and integrates quantitative approaches that have become very popular in recent years: Goal Driven Measurements (GQM), Business Process Management (BPM), Lean Methodology, and the Balanced Score Card. It presents practical methodology that allows organizations to build a measurements framework with the ability to not just monitor the events but to continuously improve and refine them by providing a feedback loop for analysis, goal, and strategy adjustments. This measurement framework is linked to an organization's overall strategy and quantitative achievement information is fed back to that strategy'--
Includes bibliographical references and index.
Keywords: Organizational effectiveness; Management; Performance